Ultrasonography and duplex doppler ultrasonography based indices in nodular thyroid disease - ASLAN, MUHAMMED; ÇİMŞİT, NURİ ÇAGATAY; GÜLLÜOĞLU, MAHMUT BAHADIR (My University, 2013)
Background. Fine needle aspiration biopsy (FNAB) is an important tool in the diagnosis of thyroid nodules. Aim. Our aim was to investigate the malignancy criteria in thyroid nodules by gray-scale ultrasonography (US) and duplex Doppler ultrasonography (DDUS), and their usefulness in reducing the number of unnecessary FNAB’s. Study design. This was a prospective observational study. Subjects and methods. 181 benign and 18 malignant thyroid nodules were evaluated by US and DDUS before FNAB or thyroidectomy. US was used to note size, shape, internal structure, nodule echogenicity, marginal properties, peripheral hypoechogenic halo, and microcalcifications. DDUS studies were used to evaluate the maximum and minimum flow velocity (Vmax and Vmin), systolic/diastolic flow velocity ratio (S/D), pulsatility index (PI), resistive index (RI), acceleration time (AT) and acceleration value. Results. Contour irregularity, size and presence of microcalcifications (p<0.001, p=0.02 and p=0.002, respectively) and S/D, Vmin, PI, RI and AT were significantly different (p=0.004, p=0.007, p=0.032, p=0.003 and p=0.003, respectively) were significant for malignant nodules. Benign and malignant nodules with or without suspicious US findings had similar DDUS findings. Vmax, Vmin, PI, RI, and AT were significantly different in the presence of microcalcification (p=0.043, p=0.001, p=0.031, p=0.04, and p=0.019 respectively). AT was significantly different in the case of absence of microcalcification (p=0.019). Comparing the irregular margins, Vmin, PI and RI were significantly different (p=0.014, p=0.003, and p=0.014 respectively). Conclusion. Benign and malignant thyroid nodules can be differentiated using gray-scale US findings and DDUS based indices together to reduce the number of unnecessary FNAB’s.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; thyroid; thyroid cancer; ultrasonography; duplex Doppler ultrasonography; thyroid nodule; acceleration time; FINE-NEEDLE-ASPIRATION; CONVENTIONAL ULTRASONOGRAPHY; DIFFERENTIAL-DIAGNOSIS; PREDICTING MALIGNANCY; GRAY-SCALE; CARCINOMA; US; SONOGRAPHY; BENIGN; ULTRASOUND; thyroid; thyroid cancer; ultrasonography; duplex Doppler ultrasonography; thyroid nodule; acceleration time.